AB1151 Polymyalgia rheumatica. new therapeutic strategy based on low dose of metrotexate plus local infiltration with corticosteroids. (12th June 2018) - Retuerto Guerrero, M.; Rodriguez, E.; Melchor, S.; Costas, N.; Pablos, J.L.; Fernández Dapica, P.
Abstract : Background: The polymyalgia rheumatica is a rheumatic inflammatory disease more frequent in the eldest population The classic therapy is based on medium doses of corticosteroids followed by a maintenance phase of low doses, generally lasting form 1–2 years. Recurrences frequently require an escalation of dose, thus lengthening the treatment time, and that entails important comorbidity. Methotrexate (MTX) has been tested in 3 randomised clinical trials, showing in two of them the efficacy as a steroid sparing agent, but it has never been tested as monotherapy. Objectives: To analyse the results of an alternative therapy in order to avoid the oral corticotherapy through the use of low dose of MTX and joint infiltration with a total duration of 24 months. Methods: A prospective observational study in which patients that had been diagnosed with 2012 EULAR/ACR criteria were evaluated in outpatient medical consultations of Rheumatology at "Doce de Octubre" Hospital between 2015–2017, with the restriction of not having received previous steroid treatment. Right after diagnosis, the treatment with MTX 5–7.5 mg/w plus the infiltration of triamcinolone acetonide in both shoulders begins, being repeated if necessary after 15 or 30 days, or in case of subsequent relapse. Results: 26 patients were included, with an average follow-up 19±5 months. 12–24 The age average at diagnosis was 74±7 years, 55–83 being 56% women. 73% had symmetrical hand arthritis and 27% structural pathology of the rotator cuff. 96% had moderate-severe pain (VAS) in shoulders, 73% in hips and 54% in hands. These percentages after a month of treatment were 15%, 11.5% and 7.7%. From the onset of symptoms until the start of treatment 104±54 days passed, 30–180 applying an initial dose of 5 mg of MTX in half of cases and 7.5 mg in the other half. There are no significant differences between precocity of the treatment or initial dose regarding a faster remission. The average of infiltrations in the shoulder per year is 2±1.4 (1–4). 25% of patients showed reactivation with good response to the MTX dose increase [maximum dose 8±1.7 (5–12.5)] plus/or joint infiltration. The average time until the revision (subjective clinical evaluation, HAQ and APR) was 2.7±1 months, 1–6 being significantly higher (p<0.05) in patients with peripheral arthritis 3.3±1.9 vs 1.3±0.7. The change of HAQ, CRP and other variables are indicated in the table. The treatment was stopped in 12% because of adverse effects (digestive intolerance, alopecia and respiratory infection in a patient with COPD). A patient showed mild plaquetopenia in wich not necessary to suspend the treatment with MTX. 8 patients were monitored during ≥2 years, in 87% of them MTX has been removed with an average follow-up after the suspension of 3±1.7 months 1–6 with no need to restart it in any case. Conclusions: The use of low dose of MTX and local joint infiltration with corticosteroids (initial and on demand) is an efficient therapeutic strategy with a low complication rate in PMR. All these results must be confirmed with controlled studies and a longer period of follow-up after the suspension of treatment. Disclosure of Interest: None declared